Bioactive peptides from salmon aquaculture processing by-product affect growth performance, plasma biochemistry, gut health, and stress resistance of gilthead seabream (Sparus aurata) - Elisa Benini; Eliana Musmeci; Serena Busti; Elena Biagi; Sara Ciulli; Enrico Volpe; Francesca Errani; Åge Oterhals; Odd Helge Romarheim; Tone Aspevik; Francesco Dondi; Giulio Zanaroli; et al. (Aquaculture Reports)
The objective of this study is to evaluate the effects of incorporating bioactive peptides (BPs) from salmon processing by-product into the diets of gilthead seabream (Sparus aurata), assessing key parameters including growth performance, blood biochemistry, immune-related gene expression, and gut health. Furthermore, the investigation explores potential advantages within the climate change context, providing a comprehensive understanding of the diverse implications associated with this dietary approach. Three distinct diets with varying BP levels (0 % [BP0], 5 % [BP5], 10 % [BP10]) as substitutions for fish meal (FM) were administered to triplicate fish groups over a 58-day trial period. Following the trial, fish were exposed to suboptimal environmental conditions (high water temperature, low oxygen) for 7 days. Analysis of growth and somatometric parameters revealed no significant differences among fish fed the three experimental diets. Additionally, the highest dosage of BP (BP10) induced a significant increase of bacterial α-diversity, suggesting potential benefits. Moreover, the expression of immune genes suggested a generally stable immune response in fish before (T1) and after (T2) challenging environmental conditions. However, the lower expression of ferritin and C3 hints toward a possible alteration of immune response in fish fed BP10 after environmental stress Additionally, challenging environmental conditions combined with high dietary inclusion of BP (10 %) triggered a physiological stress response, evidenced by elevated glucose, creatinine and uric acid levels, potentially indicating impairment of kidney function and reduced fish fitness. Furthermore, when singularly correlating gut microbiome and plasma analyses, data showed that higher presence of Stenotrophomonas and Acinetobacter families were positively related to higher lactate hematic concentration, suggesting a physiological distress caused by the inclusion of 10 % of BP in seabream diet exacerbated by adverse environmental conditions. Overall, while BP inclusion offers a sustainable alternative protein source, incorporating more than 5 % in the diet might compromise fish health under challenging environmental conditions.